Zirconium dioxide reinforced phase-containing molybdenum-rhenium alloy capable of inhibiting abnormal growth of crystal grains and preparation process of zirconium dioxide reinforced phase-containing molybdenum-rhenium alloy

Through liquid phase doping and ZrO2 particles addition, the problem of insufficient material performance when the rhenium content in molybdenum rhenium alloy is solved, and the grain size regulation and material performance are improved.

CN119433261APending Publication Date: 2025-02-14HENAN UNIV OF SCI & TECH +1
View PDF 0 Cites 3 Cited by

Patent Information

Application Number
CN202411698701.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-26
Publication Date
2025-02-14

AI Technical Summary

Technical Problem

When the rhenium content in molybdenum rhenium alloy is low, the recrystallization temperature of the material is low and the ductility is insufficient, resulting in poor mechanical properties. Traditional mechanical mixing methods lead to abnormal growth of grains, affecting the toughness of the material.

Method used

Liquid-phase doping technology is used to achieve atomic mixing of molybdenum and rhenium. By adding ZrO2 particles and optimizing the annealing process, the grain size and microstructure are regulated to form a more uniform microstructure.

Benefits of technology

It effectively suppresses the abnormal growth of grains, improves the recrystallization temperature, tensile strength and elongation of molybdenum-rhenium alloy, and improves the mechanical properties and toughness of the material.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119433261A_ABST
    Figure CN119433261A_ABST
Patent Text Reader

Abstract

The preparation process comprises the following steps: dissolving ammonium dimolybdate, ammonium rhenate and water at a high temperature, then adding zirconium hydroxide, uniformly mixing, carrying out vacuum drying, carrying out two-stage hydrogen reduction on the obtained precursor composite powder, and carrying out vacuum drying to obtain the zirconium dioxide reinforced phase-containing molybdenum-rhenium alloy capable of inhibiting abnormal growth of crystal grains, thereby obtaining the zirconium dioxide reinforced phase-containing molybdenum-rhenium alloy capable of inhibiting abnormal growth of crystal grains. Zirconium oxide reinforced molybdenum-rhenium composite powder obtained after reduction is subjected to cold isostatic pressing, pressureless sintering and hot isostatic pressing to obtain zirconium oxide reinforced molybdenum-rhenium alloy, and then the zirconium oxide reinforced molybdenum-rhenium alloy is obtained through high-temperature rolling and recrystallization annealing treatment. According to the method, atomic-level mixing of molybdenum and rhenium is achieved through liquid-phase doping, the microstructure of the molybdenum-rhenium alloy is more uniform and fine due to addition of ZrO2, the recrystallization temperature is increased, and the phenomenon that sintered grains of the molybdenum-rhenium alloy grow abnormally is relieved. And by optimizing the annealing process and regulating and controlling the annealing mode, grains are rearranged to form a more uniform microstructure, abnormal growth of the grains is further inhibited, and the high-temperature tensile strength and the ductility of the molybdenum-rhenium alloy are improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of molybdenum alloy preparation, and in particular relates to a molybdenum-rhenium alloy containing a ZrO2 reinforcement phase for inhibiting abnormal grain growth and a preparation process thereof. Background Art

[0002] Molybdenum and its alloys are widely used in electronic devices, semiconductor thin film integrated circuits, chemical reactors, nuclear reactors and other fields due to their high strength, low thermal expansion coefficient, good thermal conductivity and resistance to liquid metal corrosion. Adding a high content of rhenium to pure molybdenum can significantly increase the recrystallization temperature, ultimate tensile strength and room temperature ductility of molybdenum alloys. However, rhenium is expensive and its output is scarce, which limits its large-scale use. When the rhenium content in the molybdenum alloy is low, the molybdenum-rhenium alloy has a low recrystallization temperature and insufficient ductility, which greatly limits the further development of molybdenum-rhenium alloys in industrial applications.

[0003] At present, the preparation method of molybdenum-rhenium alloy usually adopts mechanical mixing, high-temperature reduction and pressing of molybdenum powder oxide and ammonium rhenate or rhenium powder. The molybdenum-rhenium composite powder particles prepared by mechanical mixing alone are agglomerated and entangled, and the molybdenum element and rhenium element cannot be completely dissolved, resulting in the low density of the prepared molybdenum-rhenium alloy, high oxygen content, and abnormal grain size growth during sintering. This abnormal growth of matrix grain size makes the internal microstructure of the alloy uneven, which is easy to cause stress concentration, significantly reduces the toughness of the material, and seriously affects the mechanical properties of the molybdenum-rhenium alloy. Adding ZrO2 particles to the molybdenum-rhenium alloy can not only increase the recrystallization temperature of the alloy, but also effectively improve the phenomenon of abnormal grain growth during sintering. However, the secondary phase ZrO2 particles added by the traditional method are large in size and distributed on the grain boundaries, which inevitably reduces the ductility of the material. Therefore, it is necessary to develop a preparation process for molybdenum-rhenium alloy that can inhibit abnormal grain growth, so as to regulate the grain size of the molybdenum-rhenium alloy, inhibit abnormal grain growth, and to a certain extent improve the recrystallization temperature, high-temperature tensile strength and elongation of the molybdenum-rhenium alloy. Summary of the invention

[0004] In order to solve the above problems, the present invention provides a molybdenum-rhenium alloy containing a ZrO2 reinforcement phase that inhibits abnormal grain growth and a preparation process thereof. Liquid phase doping is used to achieve atomic-level mixing of molybdenum and rhenium, solving the problem of agglomeration and entanglement of molybdenum-rhenium composite powder particles prepared by traditional mechanical mixing methods, and the inability of molybdenum and rhenium elements to be completely dissolved. The addition of second-phase particles (ZrO2) makes the microstructure of the molybdenum-rhenium alloy more uniform and fine, and the recrystallization temperature is increased, which effectively slows down the abnormal growth of sintered grains of traditional molybdenum-rhenium alloys. By optimizing the annealing process and regulating the annealing method, the grains are rearranged to form a more uniform microstructure, solving the problem of abnormal grain growth during the annealing process of the molybdenum-rhenium alloy, and improving the high-temperature tensile strength and elongation of the material.

[0005] The present invention is specifically implemented by the following technical scheme. According to the present invention, a preparation process of a molybdenum-rhenium alloy for inhibiting abnormal grain growth comprises the following steps: (1) Add ammonium dimolybdate, ammonium rhenate and water in a mass ratio of (80-100):(3-12):(150-300) into a beaker, then place the beaker into a constant temperature water bath at 200-300°C, keep the temperature at this temperature for 3-5 hours, and stir continuously while keeping the temperature to obtain an aqueous solution A; add zirconium hydroxide with a particle size of 30-200 nm into the aqueous solution A, the mass of zirconium hydroxide added being 0.3-1.2% of the mass of the above ammonium dimolybdate, and stir thoroughly to obtain a completely mixed aqueous solution B; (2) placing the beaker containing the aqueous solution B in a vacuum drying oven and drying to obtain a precipitate, crushing the precipitate to less than 300 meshes to obtain a precursor composite powder, and subjecting the precursor composite powder to two-stage hydrogen reduction to obtain a zirconium oxide reinforced molybdenum-rhenium composite powder; (3) subjecting the obtained zirconium oxide reinforced molybdenum-rhenium composite powder to cold isostatic pressing, pressureless sintering, and hot isostatic pressing in sequence to obtain a zirconium oxide reinforced molybdenum-rhenium alloy with a density greater than 98%; (4) subjecting the obtained zirconium oxide reinforced molybdenum-rhenium alloy to high temperature rolling to obtain a high-strength molybdenum-rhenium alloy plate; (5) The obtained high-strength molybdenum-rhenium alloy plate is subjected to recrystallization annealing treatment. During the recrystallization annealing treatment, a hydrogen atmosphere protection is added. The recrystallization annealing temperature is 1400-1500°C, and the annealing time is 0.5-3 h, so as to obtain a recrystallized molybdenum-rhenium alloy containing a ZrO2 reinforcement phase.

[0006] Preferably, the stirring rate in step (1) is 0-300 r / min.

[0007] Preferably, the drying temperature in step (2) is 80-120°C and the drying time is 36-72 h; the temperature of the first stage of hydrogen reduction of the precursor composite powder is 350-550°C and the hydrogen flow rate is 15-18 m 3 / h, the holding time is 4~9 h; the temperature of the second stage hydrogen reduction is 800~950℃, the hydrogen flow rate is 18~25 m 3 / h, keep warm for 8~12 h.

[0008] Preferably, in step (3), the cold isostatic pressing of the pressed blank is performed using a cold isostatic press at a pressure of 180-200 MPa and the pressure is maintained for 20-30 min; the pressureless sintering is performed using a pressureless medium frequency furnace and hydrogen is introduced, the sintering temperature is 2100-2300°C, the holding time is 4-10 h, and the hydrogen flow rate is 15-20 m 3 / h; hot isostatic pressing adopts a hot isostatic press, the pressure during hot isostatic pressing is 120~180MPa, the temperature is 1800~1950℃, the heating rate is 7~10℃ / min, and the holding time is 0.5~2 h.

[0009] Preferably, the blanking temperature of the high temperature rolling in step (4) is 1350-1500°C, cross rolling is adopted, the single deformation amount is 20-30%, and the total deformation amount is >70%.

[0010] Preferably, the hydrogen flow rate in step (5) is 18-25 m 3 / h.

[0011] In the recrystallized molybdenum-rhenium alloy containing ZrO2 reinforcement phase prepared according to the above method, molybdenum atoms and rhenium atoms are completely dissolved together without obvious agglomeration phenomenon. Its tensile strength at 1200°C is 600~650 MPa and its elongation is 16~25%.

[0012] The present invention also provides a molybdenum-rhenium alloy containing a ZrO2 reinforcement phase prepared according to the above method and its application in nuclear reactors and high-temperature and high-pressure extreme environments.

[0013] Compared with the prior art, the present invention has obvious advantages and beneficial effects. By means of the above technical solution, the present invention can achieve considerable technical progress and practicality, and has a wide range of utilization value, and has at least the following advantages: (1) The present invention provides a molybdenum-rhenium alloy containing a ZrO2 reinforcement phase that inhibits abnormal grain growth and a preparation process thereof, wherein ammonium dimolybdate and ammonium rhenate are dissolved in water, and the ammonium dimolybdate and ammonium rhenate are decomposed by heating in a constant temperature water tank to form an aqueous solution containing molybdenum and rhenium, and then zirconium hydroxide particles with a particle size of 30-200nm are added to the aqueous solution, and a completely mixed and uniform aqueous solution is obtained after sufficient stirring, and then the oxide-reinforced molybdenum-rhenium composite powder is obtained after drying, crushing, and reduction. The present invention uses liquid phase doping to achieve atomic-level mixing, so that molybdenum atoms and rhenium atoms undergo a more complete solid solution reaction, solving the problem that the molybdenum-rhenium composite powder prepared by the traditional mechanical mixing method is agglomerated and entangled, and the molybdenum element and the rhenium element cannot be completely dissolved.

[0014] (2) The present invention first performs cold isostatic pressing and pressureless sintering when preparing the molybdenum-rhenium alloy, and then performs hot isostatic pressing again, which greatly improves the density of the molybdenum-rhenium alloy. The secondary phase is added by liquid-liquid doping, so that the second phase particles are dispersed inside the grains, making the microstructure of the molybdenum-rhenium alloy more uniform and fine, effectively slowing down the abnormal growth of sintered grains of traditional molybdenum-rhenium alloys, and avoiding the reduction of ductility. At the same time, the addition of second phase particles increases the recrystallization temperature of the molybdenum-rhenium alloy, solves the problem of insufficient strength and poor room temperature brittleness of the molybdenum-rhenium alloy when the rhenium content is low, and reduces production costs.

[0015] (3) The annealing process provided by the present invention can suppress the phenomenon of abnormally coarse grains of molybdenum-rhenium alloy during annealing. During vacuum annealing at 1100-1200°C, the molybdenum-rhenium alloy still showed coarse grains and heterogeneous grain growth (comparative example). By optimizing the annealing process and regulating the annealing method, the grains are rearranged to form a more uniform microstructure, the toughness of the material is improved, and the problem of abnormal grain growth during the annealing of the molybdenum-rhenium alloy is solved.

[0016] (4) The oxide-reinforced molybdenum-rhenium alloy prepared by the present invention has a more uniform microstructure and better performance. It not only improves the recrystallization temperature of the molybdenum-rhenium alloy, but also has good tensile strength and ductility. The high-temperature tensile strength of the molybdenum-rhenium alloy containing ZrO2 reinforcement phase prepared at a recrystallization annealing temperature of 1400-1500°C can reach more than 600 MPa, and the elongation can reach more than 16%, which solves the problem of insufficient elongation of the alloy in the case of low rhenium content in the molybdenum-rhenium alloy. BRIEF DESCRIPTION OF THE DRAWINGS

[0017] Figure 1 is a SEM image of the precursor composite powder prepared in Examples 1-3 and the composite powder prepared in the comparative example; Figure 2 1 is a SEM image of the zirconium oxide reinforced molybdenum-rhenium alloy B prepared in Examples 1-3 and the molybdenum-rhenium alloy M prepared in the comparative example; Figure 3 1 is a SEM image of the recrystallized molybdenum-rhenium alloy containing ZrO2 reinforcement phase prepared in Examples 1-3 and the molybdenum-rhenium alloy D prepared in the comparative example; Figure 4 It is a stress-strain curve diagram of the recrystallized molybdenum-rhenium alloy containing ZrO2 reinforcement phase prepared in Examples 1-3 and the molybdenum-rhenium alloy D prepared in the comparative example at 1200°C. DETAILED DESCRIPTION

[0019] In order to make the purpose, technical solution and advantages of the embodiments of the present invention clearer, the technical solution of the present invention will be clearly and completely described below in conjunction with specific embodiments. Obviously, the described embodiments are part of the embodiments of the present invention, not all embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0020] The present invention is described in detail with specific examples below. If no specific conditions are specified in the following examples, they are all carried out according to conventional conditions or conditions recommended by the manufacturer. The raw materials and reagents used without specifying the manufacturer are all conventional products that can be purchased from the market.

[0021] Example 1 (1) 1670 g of ammonium dimolybdate, 70 g of ammonium rhenate and 3400 ml of water were added to a beaker, and the beaker was placed in a constant temperature water tank at 220°C for 4 h. The beaker was stirred continuously at a stirring rate of 180 r / min to obtain aqueous solution A. 6.5 g of zirconium hydroxide with a particle size of 30-200 nm was added to aqueous solution A, and after sufficient stirring, a completely mixed aqueous solution B was obtained. (2) The beaker containing aqueous solution B was placed in a vacuum drying oven at 80°C and dried for 72 h to obtain a precipitate, which was crushed to less than 300 mesh to obtain a precursor composite powder. The precursor composite powder was subjected to two-stage hydrogen reduction, wherein the temperature of the first stage of hydrogen reduction was 550°C and the hydrogen flow rate was 17 m / s. 3 / h, keep warm for 8 h; the temperature of the second stage hydrogen reduction is 925℃, the hydrogen flow rate is 22 m 3 / h, and heat preservation for 10 h; after reduction, zirconium oxide reinforced molybdenum-rhenium composite powder with a particle size of 360 nm was obtained; (3) The obtained zirconia reinforced molybdenum-rhenium composite powder was pressed at 180 MPa in a cold isostatic press for 20 min, and then sintered in a pressureless medium frequency furnace at a sintering temperature of 2300°C and a holding time of 4 h to obtain a zirconia reinforced molybdenum-rhenium alloy A with a density of 92.5%; the zirconia reinforced molybdenum-rhenium alloy A was pressed in a hot isostatic press at 120 MPa, a temperature of 1950°C, a heating rate of 8°C / min, and a holding time of 1 h to obtain a zirconia reinforced molybdenum-rhenium alloy B with a density of 99.6%; (4) The obtained zirconia reinforced molybdenum-rhenium alloy B was subjected to billet rolling at 1350°C, two passes in one heat, cross rolling, a single deformation of 30%, three passes, and a total deformation of 78.2%, to obtain a high-strength molybdenum-rhenium alloy plate; (5) The obtained high-strength molybdenum-rhenium alloy plate was subjected to recrystallization annealing treatment at a temperature of 1450°C and a holding time of 1 h. During the recrystallization annealing treatment, hydrogen atmosphere protection was added and the hydrogen flow rate was 18 m 3 / h, a recrystallized molybdenum-rhenium alloy containing a ZrO2 reinforced phase was obtained. After testing, the tensile strength of the recrystallized molybdenum-rhenium alloy containing a ZrO2 reinforced phase at 1200°C was 618.8 Mpa, and the elongation was 21.9%.

[0022] Example 2 The difference from Example 1 is that: Step (1) 1500 g of ammonium dimolybdate, 200 g of ammonium rhenate and 3200 ml of water were added to a beaker, and the beaker was placed in a constant temperature water bath at 240°C for 3 h with a stirring rate of 200 r / min; the mass of zirconium hydroxide added was 15.5 g; The temperature of the first stage of hydrogen reduction in step (2) is 500°C and the hydrogen flow rate is 17 m 3 / h, keep warm for 7 h; the temperature of the second stage hydrogen reduction is 950℃, the hydrogen flow rate is 25 m 3 / h, keep warm for 8 h; In step (3), the pressure of cold isostatic pressing of the compact is 200 MPa, and the pressing time is 25 min; the temperature of pressureless sintering is 2200°C, and the holding time is 5 h, to obtain a zirconia-reinforced molybdenum-rhenium alloy A with a density of 93.6%; the pressure of hot isostatic pressing is 160 MPa, the temperature is 1900°C, the heating rate is 8°C / min, and the holding time is 2 h, to obtain a zirconia-reinforced molybdenum-rhenium alloy B with a density of 99.2%; In step (4), the temperature of the slab rolling is 1400° C., the single deformation is 20%, the rolling is performed for 4 times, and the total deformation is 76.8%, thereby obtaining a high-strength molybdenum-rhenium alloy plate; In step (5), the annealing temperature is 1500°C, the holding time is 1 h, and the hydrogen flow rate is 16 m 3 / h, the tensile strength of the recrystallized molybdenum-rhenium alloy containing ZrO2 reinforcement phase is 635.8 MPa and the elongation is 16.3%.

[0023] Example 3 The difference from Example 1 is that: Step (1) 1576 g of ammonium dimolybdate, 144 g of ammonium rhenate and 3240 ml of water were added to a beaker, and the beaker was placed in a constant temperature water bath at 280°C for 4 h with a stirring rate of 300 r / min; the mass of zirconium hydroxide added was 13 g; The temperature of the first stage of hydrogen reduction in step (2) is 450°C and the hydrogen flow rate is 16 m 3 / h, keep warm for 8 h; the temperature of the second stage hydrogen reduction is 900℃, the hydrogen flow rate is 20 m 3 / h, keep warm for 9 hours; In step (3), the pressure of cold isostatic pressing of the compact is 180 MPa, and the pressing time is 30 min; the temperature of pressureless sintering is 2100°C, and the holding time is 8 h, to obtain a zirconia-reinforced molybdenum-rhenium alloy A with a density of 94.1%; the pressure of hot isostatic pressing is 180 MPa, the temperature is 1800°C, the heating rate is 10°C / min, and the holding time is 1 h, to obtain a zirconia-reinforced molybdenum-rhenium alloy B with a density of 99.5%; In step (4), the temperature of the slab rolling is 1500° C., the single deformation is 30%, the rolling is performed for 4 times, and the total deformation is 77.5%, thereby obtaining a high-strength molybdenum-rhenium alloy plate; In step (5), the annealing temperature is 1400°C, the holding time is 1 h, and the hydrogen flow rate is 20 m 3 / h, the tensile strength of the recrystallized molybdenum-rhenium alloy containing ZrO2 reinforcement phase is 602.4 MPa and the elongation is 20.8%.

[0024] Comparative Example (1) Molybdenum powder and rhenium powder were mixed in a dual-power mixer at a mass ratio of 95:5 at a speed of 120 r / min for 16 h to obtain a composite powder; (2) The composite powder was pressed in a 180 MPa cold isostatic press for 15 min, and then sintered in a pressureless medium frequency furnace at a sintering temperature of 2100 °C for 10 h; then pressed in a 120 MPa hot isostatic press for 2 h at a temperature of 1800 °C and a heating rate of 8 °C / min to obtain a molybdenum-rhenium alloy with a density of 95%, which was recorded as molybdenum-rhenium alloy M; (3) The molybdenum-rhenium alloy M was subjected to billet rolling at 1400°C, two passes in one heat, cross rolling, a single deformation of 30%, four passes, and a total deformation of 77.1%, to obtain a molybdenum-rhenium alloy, which was recorded as molybdenum-rhenium alloy N.

[0025] (4) The molybdenum-rhenium alloy N was subjected to vacuum annealing at a temperature of 1200°C for a holding time of 1 h to obtain a molybdenum-rhenium alloy, which was recorded as molybdenum-rhenium alloy D. After testing, the molybdenum-rhenium alloy D had a tensile strength of 498.5 MPa and an elongation of 12.1%.

[0026] Figure 1 is a SEM image of the precursor composite powder prepared in step (2) of Examples 1-3 and the composite powder prepared in step (1) of the comparative example, Figure 1 In a, b, c, and d, they correspond to Examples 1, 2, 3, and the comparative example, respectively. It can be seen that the precursor composite powder particles prepared in Examples 1-3 are nearly spherical in shape, the rhenium atoms are completely dissolved in the molybdenum atoms, and there is no obvious agglomeration phenomenon. Figure 1 (d) The prepared molybdenum-rhenium composite powder has uneven particle size, molybdenum atoms and rhenium atoms are not solid-dissolved, and agglomeration is obvious.

[0027] Figure 2 is a SEM image of the zirconium oxide reinforced molybdenum-rhenium alloy B prepared in step (3) of Example 1-3 and the molybdenum-rhenium alloy M prepared in step (2) of the comparative example, Figure 2a, b, c, and d correspond to Examples 1, 2, 3, and the comparative example, respectively. It can be seen that the zirconium oxide reinforced molybdenum-rhenium alloy B prepared in Examples 1-3 has a relatively uniform grain size. Figure 2 In the molybdenum-rhenium alloy M prepared in (d), it can be clearly seen that the grain size varies greatly and abnormal grain growth occurs.

[0028] Figure 3 The SEM images are of the recrystallized molybdenum-rhenium alloy containing a ZrO2 reinforcement phase obtained after recrystallization annealing in step (5) of Example 1-3 and the molybdenum-rhenium alloy D obtained after vacuum annealing in step (4) of the comparative example. Figure 3 In which a, b, c, and d correspond to Examples 1, 2, 3 and the comparative example, respectively, it can be seen that the recrystallized molybdenum-rhenium alloys containing ZrO2 reinforcement phase prepared in Examples 1-3 have no abnormal grain growth phenomenon, while the molybdenum-rhenium alloy D prepared in the comparative example has very obvious abnormal grain growth phenomenon.

[0029] Figure 4 It is a stress-strain curve diagram of the recrystallized molybdenum-rhenium alloy containing ZrO2 reinforcement phase prepared in Examples 1-3 and the molybdenum-rhenium alloy D prepared in the comparative example at 1200°C. Compared with the comparative example, the tensile strength of the recrystallized molybdenum-rhenium alloy containing ZrO2 reinforcement phase prepared in Examples 1-3 of the present application is increased by 103.9-137.3 MPa, and the elongation is increased by 4.2-9.8%.

[0030] The above is only an embodiment of the present invention, and does not limit the present invention in any form. The present invention can also have other forms of embodiments according to the above structures and functions, which are not listed one by one. Therefore, any simple modification, equivalent change and modification made by any technician familiar with the profession to the above embodiment according to the technical essence of the present invention without departing from the scope of the technical solution of the present invention still falls within the scope of the technical solution of the present invention.

Claims

1. A process for preparing a molybdenum-rhenium alloy containing a ZrO2 reinforcement phase and suppressing abnormal grain growth, characterized in that The following steps are involved: (1) Add ammonium dimolybdate, ammonium rhenate and water in a mass ratio of (80-100):(3-12):(150-300) into a beaker, then place the beaker into a constant temperature water bath at 200-300°C, keep the temperature at this temperature for 3-5 hours, and stir continuously while keeping the temperature to obtain an aqueous solution A; add zirconium hydroxide with a particle size of 30-200 nm into the aqueous solution A, the mass of zirconium hydroxide added being 0.3-1.2% of the mass of the above ammonium dimolybdate, and stir thoroughly to obtain a completely mixed aqueous solution B; (2) placing the beaker containing the aqueous solution B in a vacuum drying oven to dry to obtain a precipitate, crushing the precipitate to obtain a precursor composite powder, and subjecting the precursor composite powder to two-stage hydrogen reduction to obtain a zirconium oxide reinforced molybdenum-rhenium composite powder; (3) subjecting the obtained zirconium oxide reinforced molybdenum-rhenium composite powder to cold isostatic pressing, pressureless sintering, and hot isostatic pressing in sequence to obtain a zirconium oxide reinforced molybdenum-rhenium alloy with a density greater than 98%; (4) subjecting the obtained zirconium oxide reinforced molybdenum-rhenium alloy to high temperature rolling to obtain a high-strength molybdenum-rhenium alloy plate; (5) The obtained high-strength molybdenum-rhenium alloy plate is subjected to recrystallization annealing treatment. During the recrystallization annealing treatment, a hydrogen atmosphere is added for protection. The recrystallization annealing temperature is 1400-1500°C and the time is 0.5-3 h to obtain a molybdenum-rhenium alloy containing a ZrO2 reinforcement phase.

2. The process for preparing a molybdenum-rhenium alloy containing a ZrO2 reinforcement phase and suppressing abnormal grain growth as claimed in claim 1, characterized in that The stirring rate in step (1) is 0-300 r / min.

3. The process for preparing a molybdenum-rhenium alloy containing a ZrO2 reinforcement phase and suppressing abnormal grain growth as claimed in claim 1, characterized in that The drying temperature in step (2) is 80-120°C and the time is 36-72 h; the temperature of the first stage of hydrogen reduction of the precursor composite powder is 350-550°C and the hydrogen flow rate is 15-18 m 3 / h, the holding time is 4~9 h; the temperature of the second stage hydrogen reduction is 800~950℃, the hydrogen flow rate is 18~25 m 3 / h, keep warm for 8~12 h.

4. The process for preparing a molybdenum-rhenium alloy containing a ZrO2 reinforcement phase and suppressing abnormal grain growth as claimed in claim 1, characterized in that In step (3), the cold isostatic pressing of the pressed blank is performed using a cold isostatic press with a pressure of 180-200 MPa and a holding pressure of 20-30 min. The pressureless sintering is performed using a pressureless medium frequency furnace and hydrogen is introduced. The sintering temperature is 2100-2300°C, the holding time is 4-10 h, and the hydrogen flow rate is 15-20 m 3 / h; hot isostatic pressing adopts a hot isostatic press, the pressure during hot isostatic pressing is 120~180 MPa, the temperature is 1800~1950℃, the heating rate is 7~10℃ / min, and the holding time is 0.5~2 h.

5. The process for preparing a molybdenum-rhenium alloy containing a ZrO2 reinforcement phase and suppressing abnormal grain growth as claimed in claim 1, characterized in that In step (4), the blank opening temperature of high temperature rolling is 1350-1500°C, cross rolling is adopted, the single deformation amount is 20-30%, and the total deformation amount is >70%.

6. The process for preparing a molybdenum-rhenium alloy containing a ZrO2 reinforcement phase and suppressing abnormal grain growth as claimed in claim 1, characterized in that The hydrogen flow rate in step (5) is 18~25 m 3 / h.

7. The process for preparing a molybdenum-rhenium alloy containing a ZrO2 reinforcement phase and suppressing abnormal grain growth as claimed in claim 1, characterized in that The prepared molybdenum-rhenium alloy containing ZrO2 reinforcement phase has a tensile strength of 600~650 MPa at 1200℃ and an elongation of 16~25%.

8. A molybdenum-rhenium alloy containing a ZrO2 reinforcement phase obtained by the preparation process according to any one of claims 1 to 7.

9. Application of the molybdenum-rhenium alloy containing ZrO2 reinforcement phase as claimed in claim 8 in nuclear reactors and high temperature and high pressure extreme environments.

Citation Information

Cited By

  • Preparation method of second-phase reinforced tungsten-rhenium alloy

    CN120480211A

  • High-strength, high-hardness and wear-resistant molybdenum-based material and preparation method thereof

    CN120758755A

  • A method for preparing molybdenum-rhenium alloy from molybdenum concentrate roasting leaching solution and its application

    CN122629333A